2021
DOI: 10.3390/ma14195475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Bio-Based Rigid Polyurethane Foam with High Amounts of Sunflower Press Cake Particles

Abstract: In the current study, rigid polyurethane foam (PUR) was modified with 10–30 wt.% sunflower press cake (SFP) filler, and its effect on performance characteristics—i.e., rheology, characteristic foaming times, apparent density, thermal conductivity, compressive strength parallel and perpendicular to the foaming directions, tensile strength, and short-term water absorption by partial immersion—was evaluated. Microstructural and statistical analyses were implemented as well. During the study, it was determined tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These reactions may become nucleation sites. The ability of some fillers of becoming nucleating centers was described by Kairytė and coworkers [ 26 ]. According to these authors, the filler attaches itself to the cell wall, encapsulating blowing gas, and then becoming a nucleation site, which can weaken and even break up cell edges, due to the weak interaction between NCO groups and OH groups of the filler.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions may become nucleation sites. The ability of some fillers of becoming nucleating centers was described by Kairytė and coworkers [ 26 ]. According to these authors, the filler attaches itself to the cell wall, encapsulating blowing gas, and then becoming a nucleation site, which can weaken and even break up cell edges, due to the weak interaction between NCO groups and OH groups of the filler.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, to previous studies [ 7 ], the addition of dust causes the formation of cells of much smaller sizes. Kairyte et al [ 2 ] also observed that the addition of fillers caused the reduction in the size of the average cell. In general, it can be stated that the use of filler reduced the cell cross-sectional area.…”
Section: Resultsmentioning
confidence: 99%
“…Polyurethane foams (PUR) are the product of the polyaddition reaction between polyols and isocyanates with other additives [ 1 ]. Because of their broad range of properties, PUR are commonly used in various industry branches, e.g., thermal insulating layers, furniture, and automotive seats [ 2 , 3 ]. There are two main types of foam: rigid foam and flexible polyurethane foam [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, at this sample, this more compact cellular structures assured an influential stress distribution throughout the matrix during the compression. 65 On the other hand, the decrease observed when TFFs loading exceeded to 12% was probably caused by the presence of the disordered cells, flaws of the struts such as disconnection of the struts, locally accumulations in the cell walls, regional TFFs aggregates and the perforation of the cells by TFFs. 79 Furthermore, this final compressive strength reduction revealed that higher TFFs loading destroyed whole uniformity and anisotropy of the cells.…”
Section: Compression Tests Of the Produced Foamsmentioning
confidence: 96%
“…[62][63][64] The mechanical characteristics of the porous polymeric materials is affected by the content of closed cell, apparent density, free volume property and topology of filler. 65 The effectiveness of the reinforcing filler materials also highly depends on the incorporation method, 66 component incompatibility, 67 dispersion quality 68 and loading level. 69 In this aspect, in this part of the paper, the tensile tests for the produced foam samples were performed at room temperature in order to figure out whether the produced RPUFs with TFFs had an application potential for the technological and industrial areas.…”
Section: Tensile Tests Of the Produced Foamsmentioning
confidence: 99%